An experimental study on the combustion behaviours of orange peel-based solid biofuels - Kocer, Anil Tevfik; Ozcimen, Didem; Gokalp, Iskender (SPRINGER HEIDELBERG, 2024)
The usage of orange peel wastes for solid biofuel production can provide a sustainable solution for solid waste management while also reducing the negative effects of fossil fuels. The aim of this study is to compare the combustion properties of orange peel wastes and solid biofuels obtained from them. In this context, the combustion behaviour of orange peel wastes and hydrochar and biochar samples obtained as a result of their hydrothermal carbonization and pyrolysis were investigated by the thermogravimetric method in this study. In addition, the combustion kinetics of these fuels were determined using the Kissinger-Akahira-Sunosa (KAS) and Flynn-Wall-Ozawa (FWO) methods. As a result of the thermogravimetric analysis, it is seen that the combustion behavior of raw biomass and hydrochar are quite similar, but the combustion of biochar is different from them. The combustion of raw waste and its hydrochar took place in multiple steps, the combustion of biochar took place in a single step. While the average combustion activation energy values of orange peel, hydrochar and biochar were calculated by KAS method as 159.876, 208.561 and 77.656 kJ/mol, respectively; they were calculated by the FWO method as 161.717, 208.600 and 85.209 kJ/mol, respectively. According to these results, the production of biochar from orange peel wastes by pyrolysis and the use of the obtained biochars in combustion systems are more suitable in terms of energy efficiency. Future research of the combustion of solid biofuels from orange peel will be very important to determine their potential for use in combustion systems, either directly or as an additive, and to increase energy efficiency.
Keywords: Orange peel; Biochar; Hydrochar; Combustion kinetics; Thermogravimetry; ARTIFICIAL NEURAL-NETWORK; URIC-ACID; HYDROTHERMAL CARBONIZATION; BACILLUS-CEREUS; OPTIMIZATION; KINETICS; PURIFICATION; PYROLYSIS; IDENTIFICATION; Energy & Fuels; Engineering